Ageism and gatekeeping: My experiences as an early career academic at a historically black university in South Africa - Maluleka, Paul (Critical Studies in Teaching and Learning, 2024)
In 2019, senior black academics wrote about their experiences as members of faculty at historically white universities (see Khunou, et al., 2019). These experiences were reflective of the authors’ encounters with the legacies of colonialism, apartheid, and neoliberal capitalism. However, often experiences of academics from historically black universities (HBUs), especially early career academics (ECA), are marginalised and excluded. Using intersectionality and Nat Nakasa’s ‘native of nowhere’ as theoretical lenses and an autoethnographic reflexivity approach as the methodological approach, I narrate my encounters with ageism and gatekeeping at a HBU as a New Generation of Academics Programme academic. I argue that the intersectionality between ageism and gatekeeping made me feel like a native of nowhere. I equally conclude that moving forward there is a need to foster a sense of belonging among ECAs through enacting decolonial love. This requires that senior (black) academics not to perpetuate similar violent experiences they endured. This way, ECAs can become natives of somewhere within the university.